PENERAPAN METODE MONTESSORI BERBANTU MEDIA SANDPAPER LETTERS UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Misnar Dumapuan Lubis; Abd. Manap HT Uruk; Sutan Botung Hasibuan (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to improve the learning process and students’ learning outcomes through the implementation of the Montessori method assisted by Sandpaper Letters media among first-grade students at Elementary School Negeri 1007 Tanjung Baringin. The study employed a Classroom Action Research (CAR) approach with a two-cycle design consisting of planning, action, observation, and reflection stages. The research participants were 25 first-grade students. Data were collected through observation, learning outcome tests, and documentation. Data analysis was conducted using descriptive quantitative techniques for test results and descriptive qualitative analysis for observational data. The findings indicate changes in students’ learning outcomes from the pre-cycle to Cycle II following the implementation of the Montessori method assisted by Sandpaper Letters. These changes are associated with increased student engagement in learning activities through concrete and multisensory experiences that align with the developmental characteristics of lower-grade elementary students. This study provides empirical evidence that the Montessori method assisted by Sandpaper Letters media, within a CAR framework, can serve as an approach to improving learning practices in lower elementary classrooms.